ChemInform Abstract: Synthesis of Surface‐Active N‐Heterocyclic Carbene Ligand and Its Pd‐Catalyzed Aqueous Mizoroki—Heck Reaction. Issue 43 (7th October 2016) - Taira, Toshiaki; Yanagimoto, Takaya; Sakai, Kenichi; Sakai, Hideki; Endo, Akira; Imura, Tomohiro
Abstract: The title agent and its Pd complex act as a general surfactant: hydrophobic oily substrates are emulsified in water and thus, an acceleration of the reaction becomes possible under heterogeneous conditions.